The Multifractal Load Balancing Method - Radivilova, T.; Ivanisenko, I. (KHARKIV NATIONAL UNIVERSITY OF RADIO ELECTRONICS, 2015)
The load-balancing system, built on the basis of a subsystem load balancer and subsystem control and monitoring that closely interact with each other was propose in work. This system is presented as a queuing system with priority service discipline. In the described queuing system parallel processing flow applications occur in the multiple serving devices and successive junction of them into unified stream is done. The method of multifractal load balancing is submited on the basis of the developed system of load balancing.
Keywords: load balancing; distributed system; queuing system; multifractal traffic; resource utilization; self similar